The Influence of Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) on ROA in Banking Companies Listed on the Indonesian Stock Exchange Period 2018-2022 - Anjelika Bella Cantika; Maxqulin; Merry Rusida S (International Journal of Scientific Multidisciplinary Research, 2024)
Examining and assessing the effects of The purpose the loan to deposit ratio (LDR) and return on assets (ROA) of financial institutions listed on the Indonesian Stock Market in relation to non-performing loans (NPL). The nature of this study methodology is quantitative. The study sample consists of ten banking organizations that are registered on the Indonesian Stock Exchange (Persero) Tbk and have financial reports covering a five-year period, from 2018 to 2022. This implies that there are a total of 50 samples (10 x 5). The study finds that for every additional person who raises the quantity of non-performing loans (NPL) (x1) while keeping the loan to deposit ratio (LDR) constant (x2), profitability will drop by an average of –1,268. This implies the existence of non-performing loans (NPL). little effect on the financial success ofbanking companies listed on the IDX; nonetheless, the profit margin will lose an average of 5,255 if the Loan To Deposit Ratio (LDR) (x2) rises by one while the Non-Performing Loans (NPL) (x1) stay the same. It is clear from this how much each predictor effects the response variables and how the Loan to Deposit Ratio (LDR) affects the profitability of banks listed on the BEI. This suggests that the criteria of Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) have a big influence on the bank profitability displayed on the IDX. Liability to Deposit Ratio (LDR) and Non-Performing Loans (NPL) together have an influence of 0.308, or 30.8%, while additional factors not covered in this study account for the remaining 69.2%